Clinical judgment of GPs for the diagnosis of dementia: a diagnostic test accuracy study. Issue 5 (2021) - Creavin, Samuel Thomas; Haworth, Judy; Fish, Mark; Cullum, Sarah; Bayer, Anthony; Purdy, Sarah; Ben-Shlomo, Yoav
No abstract available